Assessment of mechanical, fracture and thermal properties of epoxy nanocomposites reinforced with low-concentration nano Boron Carbide (B4C) (Fracture and Structural Integrity, 2025)
This study investigates the effects of low concentration (0.1-0.4 wt.%) nano-boron carbide (B4C) reinforcement on the mechanical, thermal and fracture properties of epoxy nanocomposites. The nanocomposites were prepared via solution casting using ultrasonication to ensure proper dispersion of the nanofiller. The characterisation included Fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), tensile, flexural, impact and fracture tests. Results showed significant enhancements in mechanical properties. Tensile strength peaked at 31.2 MPa (71% improvement) for 0.3 wt. % B4C, while modulus increased steadily to 1400 MPa (33% improvement). Flexural tests showed a progressive enhancement in bending strength, exhibiting 70.46 MPa (50% improvement) at 0.4 wt. % B4C. Impact strength surged by 62% at 0.4 wt. % and fracture toughness increased steadily, exhibiting 70% improvement. Thermal analysis revealed a higher glass transition temperature (Tg) and improved stability with B4C addition, attributed to restricted polymer chain mobility. SEM images showed improved fracture resistance, with rougher surfaces and smaller cleavage planes indicating effective energy absorption. Finite element (FE) simulations validated experimental tensile and flexural results, with variations within 15%. Statistical analysis confirmed all improvements were significant (p < 0.05).
Keywords: Boron carbide; Epoxy nanocomposites; Mechanical properties; Thermal properties; Fracture toughness; Finite element simulation